A review of the optimisation of the use of formalin fixed paraffin embedded tissue for molecular analysis in a forensic post-mortem setting. (November 2017) - Reid, Kate Megan; Maistry, Sairita; Ramesar, Raj; Heathfield, Laura Jane
Highlights: FFPE tissue is a valuable source of DNA in retrospective investigations. DNA obtained from FFPE tissue is highly variable in quality and quantity. DNA may be suitable for downstream molecular analyses, such as a molecular autopsy. Optimization should focus on aspects of DNA extraction and amplification. No single procedure exists through which DNA can be maximized. Abstract: Molecular analyses in a post-mortem setting are becoming increasingly common, particularly in cases of sudden unexplained death, with the aim of identifying genetic mutations which may be responsible for causing death. In retrospective investigations, the access to suitable autopsy biological samples may be limited, and often formalin fixed paraffin embedded (FFPE) tissue is the only sample available. The preservation of tissue in formalin is known to damage DNA through crosslinking activity. This results in the extraction of severely fragmented DNA of variable yields, which subsequently reduces the ability to perform downstream molecular analyses. Numerous studies have investigated possible improvements to various aspects of the DNA extraction and amplification procedures from FFPE tissue and this review aims to collate these optimization steps in a cohesive manner. A systematic review was performed of three major databases, which identified 111 articles meeting the inclusion criteria. Five main areas for optimization and improvements were identified in the workflow: (1) tissue type, (2) fixation process, (3) post-fixation, (4) DNA extraction procedure and (5) amplification. It was found that some factors identified, for example tissue type and fixation process, could not be controlled by the researcher when conducting retrospective analyses. For this reason, optimization should be performed in other areas, within the financial means of the laboratories, and in accordance with the purposes of the investigation. Implementation of one or more of the optimization measures described here is anticipated to assist in the extraction of higher quality DNA. Despite the challenges posed by FFPE tissue, it remains a valuable source of DNA in retrospective molecular forensic investigations.